Investigation Of the Incidence of Thromboembolic Complications in Patients After Transurethral Resection of the Prostate Gland with Varying Degrees of Risk on The Caprini Scale - Alibekovich, Alibekov Omar; Abdulkhamitovna, Kazanbieva Aminat; Magomedovich, Abdullaev Arslankhan; Madina Rafisovna, Aslanbekova; Rasurulaevna, Rasurulaeva Uzlipat; Kazimovna, Gadzhieva Asiyat; Radzhabovich, Azizov Marat; Alievna, Shamsudinova Raziat; Bakhtiyarovich, Dzhabrailov Dzhabrail; Saygidovich, Saidov Magomedsaygid (Journal of Neonatal Surgery, 2025)
The aim of the study is to determine the relationship between the degree of risk of thromboembolic complications on the Caprini scale and the frequency of their occurrence in patients undergoing transurethral resection of the prostate gland (TURP). A retrospective cohort study was conducted, including 312 patients with different levels of risk on the Caprini scale. It was revealed that the frequency of venous thromboembolism increases in proportion to the increase in scores on the scale. The findings emphasize the importance of using the Caprini scale in urological practice and the need for individualized thromboprophylaxis in high-risk patients.